2012
DOI: 10.1021/ml300133f
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of AM-1638: A Potent and Orally Bioavailable GPR40/FFA1 Full Agonist

Abstract: GPR40 (FFA1) is a G-protein-coupled receptor, primarily expressed in pancreatic islets, the activation of which elicits increased insulin secretion only in the presence of elevated glucose levels. A potent, orally bioavailable small molecule GPR40 agonist is hypothesized to be an effective antidiabetic posing little or no risk of hypoglycemia. We recently reported the discovery of AMG 837 (1), a potent partial agonist of GPR40. Herein, we present the optimization from the GPR40 partial agonist 1 to the structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 16 publications
1
67
0
Order By: Relevance
“…In the present study, the full FFAR1 agonists, AM-1638 (Brown et al. 2012) and AM-5262 (Wang et al. 2013), both caused a pronounced GLP-1 response, at least comparable to the response induced by intraluminal glucose (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the full FFAR1 agonists, AM-1638 (Brown et al. 2012) and AM-5262 (Wang et al. 2013), both caused a pronounced GLP-1 response, at least comparable to the response induced by intraluminal glucose (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…2014) and full agonists, AM-1638 (Brown et al. 2011, 2012; Lin et al. 2012) and AM-5262 (Wang et al.…”
Section: Methodsmentioning
confidence: 99%
“…5 Interestingly, a structurally similar compound 10 (EC 50 ¼ 1.5 μM, E max ¼ 98%) displayed full agonist properties. 24 Separation of the enantiomers revealed that 11 retained full agonism (EC 50 ¼ 4.0 μM, E max ¼ 99%) while the corresponding enantiomer was a partial agonist (EC 50 ¼ 0.65 μM, E max ¼ 47%). Moving the ether linkage from the para to meta orientation along with further optimization of the biaryl rings and the β-chiral substituent provided agonist 12 (EC 50 ¼ 0.16 μM, E max ¼ 100%).…”
Section: Gpr40 Full Agonistsmentioning
confidence: 99%
“…On the whole, the compound 13 series shared almost the same SAR with the compound 11 series (11 vs 13, 23 vs 24, 30 vs 31 and 32 vs 33). Interestingly, the introduction of gem-dimethyl group (14), however, showed a drastic loss of activity despite increased lipophilicity, suggesting that the limited space in the binding pocket around this area. Then, an initial optimization of the terminal phenyl with methyl group (15, 18, and 19) demonstrated that substitution is tolerated in all positions and preferred in the meta-substituent.…”
Section: Ffa1 Agonistic Activity and Sar Studymentioning
confidence: 99%
“…1), [9][10][11][12][13][14][15][16][17] and the compounds TAK-875, AMG-837 and LY2881835 were in clinical trials for treatment of T2DM. However, many of these agonists have relatively high molecular weight and lipophilicity (red mark in Fig.…”
Section: Introductionmentioning
confidence: 99%